Determination of optimal load in the Wingate Anaerobic Test is not depend on number of sprints included in mathematical models - Michalik, K.; Smolarek, M.; Ochmann, B.; Zaton, M. (Frontiers in Physiology, 2023)
Determining the optimal load (OPTLOAD) in measuring mechanical peak power output (PPO) is important in assessment of anaerobic fitness. The main goals of this study were: 1) to examine estimated optimal load and PPO based on a force-velocity test and 2) to compare the PPO from the previous method with the Wingate Anaerobic Test (WAnT). The study involved 15 academic male athletes, aged 22.4 ± 2.3 (years), height 178.9 ± 6.8 (cm), and body weight 77.9 ± 12.2 (kg). They performed the 30-s WAnT (7.5% of body weight) during the first visit to the laboratory. Second to fourth session included a force-velocity test (FVT) involving three, 10-s all-out sprints. A randomized load ranging from 3 to 11 kg was used in each session for FVT. The OPTLOAD and PPO were computed using quadratic relationships based on power-velocity (P-v) and power-percent of body weight (P-%BM) and including three, four, five and nine sprints from FVT. The results showed non-difference in OPTLOAD [13.8 ± 3.2 (%BM); 14.1 ± 3.5 (%BM); 13.5 ± 2.8 (%BM); 13.4 ± 2.6 (%BM)] executed at three, four, five, and nine sprints (F3,56 = 0.174, p = 0.91, ?2 = 0.01). The two-way ANOVA revealed that PPO were similar between tested models (P-%BM vs. P-v) independently from the numbers of sprints (F3,112 = 0.08, p = 0.99, ?2 = 0.000). Moreover, the PPO measured in the WAnT (870.6 ± 179.1 W) was significantly lower compared with in P-v model (1,102.9 ± 242.5-1,134.2 ± 285.4 W) (F4,70 = 3.044, p = 0.02, ?2 = 0.148). In addition, the PPO derived from P-%BM model (1,105.2 ± 245.5-1,138.7 ± 285.3 W) was significantly higher compared with the WAnT (F4,70 = 2.976, p = 0.02, ?2 = 0.145). The findings suggest the potential utility of FVT for assessment of anaerobic capacity.